Automedicación y su relación con el nivel de conocimiento de las reacciones adversas en pacientes que acuden al servicio odontológico del Hospital Regional de Loreto, 2022 - Tuesta Mejía, John Edward (2023)
Dental conditions such as toothache, gingival bleeding, discomfort and halitosis have been identified as common reasons for self-medication. Thus, the purpose of this study was to determine the mechanisms of the relationship between self-medication and knowledge of adverse reactions in a group of patients who were seen in the dental service of the Loreto regional hospital in 2022. After reviewing the background and theory, a cross-sectional observational study of causal-analytic scope was conducted. The study population consisted of 400 patients, randomly selected under probability sampling, and two structured questionnaires were applied to a sample of 197 patients. In order to verify the hypotheses, the respective Chi2 test of independence at 5% was used. The results showed that 81.2% of the patients lacked information about the negative consequences of drugs, while the tendency to self-medicate was evident in 49.7% of the situations. Finally, it was confirmed that there is a significant correlation between self-medication and the level of information that patients have about possible adverse reactions in those users who were seen in the dental service of the Loreto regional hospital during the year 2022.